An Evaluation of Moisture Damage Resistance of Asphalt Concrete based on Dynamic Creep Characteristics - Jitsangiam, P.; Nusit, K.; Nikraz, Hamid (Springer, 2019)
The performance of asphalt concrete is severely influenced by moisture. The presence of moisture in asphalt pavement substantially reduces its designed service lifetime. Currently, the indirect tensile strength test with constant loading rate is employed to estimate the moisture damage potential to an asphalt mixture. This evaluation method is empirical in nature and, therefore, suitable for only empirically designed asphalt pavements. However, speculation exists in that the conventional testing method may inappropriately simulate actual field conditions. Therefore, this research aims to evaluate the moisture damage potential to asphalt concrete under cyclic loading using the dynamic creep testing platform. The dynamic creep test provides the flow number, which represents the number of loading cycles at the failure point of the asphalt mixture. Three different types of asphalt mixtures commonly used in Western Australia were investigated in this research. The dynamic creep test provided more reasonable evaluation results of potential moisture damage than the conventional method. The tensile strength ratio of all mixtures in this research were greater than 80%, which is the conventional design criteria. On the other hand, the dynamic creep test reveals that flow number ratio of two mixtures dropped below 80%. The flow number ratio of 14 mm mixture was 58%, while 56% was obtained from 20 mm mixture. However, high uncertainty in the dynamic creep test results was observed, due to the interpretation technique. In conclusion, based on the research findings, the dynamic creep test can be used as a complementary test of the stripping potential in asphalt concrete.